High-Throughput Sequencing of Small RNAs for the Sanitary Certification of Viruses in Grapevine - Velasco, Leonardo; Padilla, Carlos V. (Frontiers in Plant Science, 2021)
Biological indexing is the method generally recognized for the certification of propagative grapevines in many countries and it is mandatory in the European Union. It consists in the evaluation of the plant material after grafting on indicators that are inspected for symptom development. This is a lengthy process that require well-trained workers, testing field, etc. Alternative diagnostics methods such as serology and RT-qPCR have been discarded for certification for their intrinsic drawbacks. In turn, high-throughput sequencing (HTS) of plant RNA has being proposed as a plausible alternative to the bioassay. But before it is accepted, different aspects of this process must be evaluated. We have compared HTS of small RNAs with bioassays and other diagnostic methods from a set of 40 grapevine plants submitted for certification. The results allowed us the identification of numerous grapevine viruses in the samples, as well as different variants. Besides, relationships between symptom expression and viromes was investigated, in particular for leafroll-associated viruses. We compared HTS results using analytical and bioinformatics approaches in order to define minimum acceptable quality standards for certification schemes, resulting in a pipeline proposal. Finally, the comparison between the HTS and the bioassay resulted favorable for the former in terms of reliability, cost and timing.